Mezi dětstvím a dospělostí, identitou a performancí: K možnostem konceptualizace fenoménu tomboye - Veronika Klusáková (Gender a Výzkum, 2012)
The study deals with tomboyism from the perspective of past and current psychiatric and sociological research, and proposes a new approach to this liminal phenomenon operating in-between binary opposites of traditional femininity and masculinity. This approach makes use of intersectional analysis developed by feminists of colour to address interlocking systems of oppression based on both race and gender, and combines it with the issue of performance and the notion of identity as fluid. It also challenges usual interpretations of tomboy narratives, as is shown on the analysis of two films with tomboyish characters – Robert Mulligan’s To Kill a Mockingbird (1962) and Céline Sciamma’s Tomboy (2011).